2021
DOI: 10.1002/mame.202100428
|View full text |Cite
|
Sign up to set email alerts
|

Development and Challenges of Thermal Interface Materials: A Review

Abstract: With the development of electronic equipment components in the direction of integration, miniaturization, and intelligence, their increasingly high heat dissipation requirements pose a high challenge to the thermal conductivity (TC) of thermal interface materials (TIMs). Polymer-based composite materials with high TC have gradually been favored because of their good processing performance, low cost, and low density. It is important to summarize the relationship between the problems of low heat conduction and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 136 publications
0
9
0
Order By: Relevance
“…Boron Nitride (BN) is a popular filler with a wide band gap and high thermal conductivity [10]. Studies showed that BN fillers with appropriate doping parameters could enhance the electrical insulation [11], thermal conductivity [12,13], mechanical strength and chemical stability of polymer materials [14,15]. The modification effect has been verified in different types of polymer matrices such as cellulose, epoxy resin, polyethylene and polyimide.…”
Section: Introductionmentioning
confidence: 99%
“…Boron Nitride (BN) is a popular filler with a wide band gap and high thermal conductivity [10]. Studies showed that BN fillers with appropriate doping parameters could enhance the electrical insulation [11], thermal conductivity [12,13], mechanical strength and chemical stability of polymer materials [14,15]. The modification effect has been verified in different types of polymer matrices such as cellulose, epoxy resin, polyethylene and polyimide.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal stability depends on the filler type, shape, size, defect, load rate, surface roughness, and the interactions between the filler and polymer matrix. 14,59,60 Some fillers can chemically interact with the functional groups of PVA, leading to covalent or intermolecular hydrogen bonding interactions, which can strengthen PVA matrices and improve the stability of the composite material under thermal stress (Figure 2). Although noncovalent bonds are not strong as covalent bonds, they can still significantly influence the properties and behaviors of PVA.…”
Section: Mechanism Of Thermal Degradationmentioning
confidence: 99%
“…Balancing the contradiction between thermal conductivity and viscoelasticity has become the key problem in the development of TIMs. Most of the literatures about TIMs mainly focus on promoting their thermal conductivity while systematic studies on their rheological behaviors are still scarce 8–11 . Before curing, TIMs always experience a large deformation which controls its minimal thickness which has great influence on the contact thermal resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literatures about TIMs mainly focus on promoting their thermal conductivity while systematic studies on their rheological behaviors are still scarce. [8][9][10][11] Before curing, TIMs always experience a large deformation which controls its minimal thickness which has great influence on the contact thermal resistance. Therefore, understanding the non-linear rheological behavior of TIMs has great significances for practical use.…”
mentioning
confidence: 99%